2009
DOI: 10.1245/s10434-009-0554-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Axillary Reverse Mapping During Sentinel Lymph Node Biopsy in Breast Cancer Patients

Abstract: Arm lymphatic drainage can be observed in the SLNB field in 37.5% of the cases. Using the ARM during SLNB may facilitate the preservation of lymphatics draining the arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 23 publications
5
93
0
Order By: Relevance
“…21 Also, similar to our results Casabona F et al, documented that the mean age in his study was 57 years with range 25-81 years, and most of them, 82% (59/72), were post-menopausal compared to 69.44% (50/72) post-menopausal patients in our study (50/72) Beek MA et al, documented in his review for many ARM studies that the visualization rate for axillary nodes and axillary lymphatics in ALND range between (39-90%) and (47-86%) respectively. 24,26 Gebruers N et al, in systemic review for lymphatic visualization mentioned that in ALND the average of detection ratio was 80.8% with range 46.6-94.9% documenting that the coloring technique (Blue dye, isotope, fluorescence) seems that it doesn't have any influence on the detection rate of ARM nodes. 27 This agree with our results where we had successful visualization of lymphatics in 86.1% of cases in the study group after injection of 2.5 ml of methylen blue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Also, similar to our results Casabona F et al, documented that the mean age in his study was 57 years with range 25-81 years, and most of them, 82% (59/72), were post-menopausal compared to 69.44% (50/72) post-menopausal patients in our study (50/72) Beek MA et al, documented in his review for many ARM studies that the visualization rate for axillary nodes and axillary lymphatics in ALND range between (39-90%) and (47-86%) respectively. 24,26 Gebruers N et al, in systemic review for lymphatic visualization mentioned that in ALND the average of detection ratio was 80.8% with range 46.6-94.9% documenting that the coloring technique (Blue dye, isotope, fluorescence) seems that it doesn't have any influence on the detection rate of ARM nodes. 27 This agree with our results where we had successful visualization of lymphatics in 86.1% of cases in the study group after injection of 2.5 ml of methylen blue.…”
Section: Discussionmentioning
confidence: 99%
“…was 16 with range (9-24) nodes. 26 Tummel E et al, mentioned that the median number for excised L.Ns. were 13.3 nodes in patients underwent ALND whether it was accompanied by SLNB or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) (Boneti et al, 2008;Casabona et al, 2008Casabona et al, , 2009Nos et al, 2007;Ponzone et al, 2008;Thompson et al, 2007). Thompson et al (2007) injected 2.5 mL of blue dye intradermally or subdermally into the upper inner arm along the medial intramuscular groove of the ipsilateral arm.…”
Section: Mapping By Blue Dye Injectionmentioning
confidence: 99%
“…Since 2000, many clinical trials have confirmed that sentinel lymph node biopsy (SLNB) is an accurate technique that permits omitting a complete axillary lymph node dissection (ALND) in selected patients while diminishing the incidence of arm and shoulder morbidity [1,2]. SLNB is developing in new directions (multifocal/multicentric tumors) [3]: applications with neoadjuvant chemotherapy [4][5][6][7][8][9][10], axillary reverse node mapping [11][12][13], and nanotechnology [14]. Axillary lymph node status is the single most significant predictive factor for patients with invasive breast tumors [15].…”
Section: Background and Objectivementioning
confidence: 99%